Eusociality influences the strength of negative selection on insect genomes. Issue 1933 (26th August 2020) - Imrit, Mohammad A.; Dogantzis, Kathleen A.; Harpur, Brock A.; Zayed, Amro
Abstract : While much of the focus of sociobiology concerns identifying genomic changes that influence social behaviour, we know little about the consequences of social behaviour on genome evolution. It has been hypothesized that social evolution can influence the strength of negative selection via two mechanisms. First, division of labour can influence the efficiency of negative selection in a caste-specific manner; indirect negative selection on worker traits is theoretically expected to be weaker than direct selection on queen traits. Second, increasing social complexity is expected to lead to relaxed negative selection because of its influence on effective population size. We tested these two hypotheses by estimating the strength of negative selection in honeybees, bumblebees, paper wasps, fire ants and six other insects that span the range of social complexity. We found no consistent evidence that negative selection was significantly stronger on queen-biased genes relative to worker-biased genes. However, we found strong evidence that increased social complexity reduced the efficiency of negative selection. Our study clearly illustrates how changes in behaviour can influence patterns of genome evolution by modulating the strength of natural selection.